Raman spectroscopic and SEM/EDXS analyses of high translucent Nantgarw porcelain. Issue 13 (October 2020) - Colomban, Philippe; Edwards, Howell G.M.; Fountain, Charles
Abstract: In the first quarter of the 19th Century the factory established at Nantgarw created some of the finest quality porcelain in the world, rivalling that of Sevres, but beset by economic difficulties resulting from extraordinarily high kiln losses approaching 90 %, the production which started in 1817 (ceased by 1820) produced the finest translucency ever achieved in Georgian porcelains. An opportunity has arisen to analyse rare Nantgarw porcelain shards excavated archaeologically from the Nantgarw China Works site. Two types of compositions, bone china and silica-rich pastes are identified by Raman and SEM-EDXS analyse, confirming some ancient studies. The spectral data from "sagged" silica-rich shards are interpreted to reveal potential explanations of the manufacturing fault which significantly contributed to the demise of the ceramics factory. Finally, the pigments and glaze used in Nantgarw porcelain decoration have been analysed and identified for the first time.